Conserved currents in the six-vertex and trigonometric solid-on-solid models. (17th March 2017) - Ikhlef, Yacine; Weston, Robert
Abstract: We construct quasi-local conserved currents in the six-vertex model with anisotropy parameter η by making use of the quantum-group approach of Bernard and Felder. From these currents, we construct parafermionic operators with spin 1 + i η / π that obey a discrete-integral condition around lattice plaquettes embedded into the complex plane. These operators are identified with primary fields in a c   =  1 compactified free Boson conformal field theory. We then consider a vertex-face correspondence that takes the six-vertex model to a trigonometric SOS model, and construct SOS operators that are the image of the six-vertex currents under this correspondence. We define corresponding SOS parafermionic operators with spins s   =  1 and s = 1 + 2 i η / π that obey discrete integral conditions around SOS plaquettes embedded into the complex plane. We consider in detail the cyclic-SOS case corresponding to the choice η = i π (   p − p ′ ) / p, with p ′ < p coprime. We identify our SOS parafermionic operators in terms of the screening operators and primary fields of the associated c = 1 − 6 (   p − p ′ ) 2 / p p ′ conformal field theory.